Effects of left ventricular function on the exercise capacity in patients with repaired tetralogy of fallot - Suchaya Silvilairat (2018)
Background: Tissue Doppler imaging has been recently used to evaluate ventricular function. Peak oxygen uptake (V ·O 2peak) has been demonstrated as a predictor for death in adults with repaired tetralogy of Fallot (TOF). The aim of this study was to determine which Doppler parameters correlated with V ·O 2peak in patients with repaired TOF. Method and Results: Doppler echocardiography, tissue Doppler imaging, and exercise test were performed in 30 patients with TOF after surgical repair. In 30 patients with repaired TOF (median age 14 years, range 9-25 years), 11 patients (37%) were female. Seven patients (median age 12 years) had normal left ventricular diastolic function, whereas the rest of the patients were classified as diastolic dysfunction grade II (median age 15 years; n = 15) and III and IV (median age 18 years; n = 8). The oxygen uptake at anaerobic threshold (V ·O 2AT) and peak exercise in patients with left ventricular diastolic dysfunction was significantly lower than that in those with normal diastolic function. Also, V ·O 2AT and V ·O 2peak in patients with diastolic dysfunction grade III and IV were significantly lower than that in those with diastolic dysfunction grade II. Left ventricular early diastolic myocardial velocity was most closely correlated to V ·O 2peak (r = 0.51; P = 0.005). Peak early ventricular filling velocity to early diastolic myocardial velocity ratio was significantly correlated with V ·O 2peak (r =-0.50; P = 0.006). Conclusion: Left ventricular diastolic dysfunction is correlated with V ·O 2peak. Left ventricular diastolic function should be a routine echocardiographic assessment in patients with repaired TOF. © 2011, Wiley Periodicals, Inc.